Human embryos cultured in vitro to 14 days. Issue 1 (January 2017) - Morris, Samantha A.
Abstract : Abstract : We know a great deal about the development of the mammalian embryo until the time that the blastocyst implants into the uterus. With model organisms such as the mouse, we have also developed a considerable understanding of development immediately around gastrulation as embryos can be recovered at this stage for short-term in vitro culture. However, the intervening period of development remained a 'black box' because it takes place as the blastocyst is implanting into the uterus. Over the past 6 years, techniques pioneered and developed in Magdalena Zernicka-Goetz's laboratory for the in vitro culture of embryos through these implantation stages have opened up this box, affording the first glimpse of embryonic development through these previously hidden stages. Remarkably, the techniques developed with mouse embryos are equally applicable to human embryos, ushering the very first opportunities for studying our own development throughout this time. Here, I outline how the culture methods were developed, paving the way to culture of the human embryo to the point of gastrulation, an accomplishment recognized as the People's Choice for the Scientific Breakthrough of 2016 in Science magazine. I also discuss the new ethical challenges raised by the possibility of extending the time limits for human embryo culture.